Membangun Sinergi: KKNI, Sistem Blok, dan Praktikum Dalam Mengatasi Stres Belajar Mahasiswa Fakultas MIPA Melalui Perspektif Psikologi Pendidikan - Subaedah, Sitti; Nainggolan, Yesi Rama Indah; Nasution, Nur Hidayati; Aisyah, Siti; Siantar, Desi Lumban (Yayasan Sagita Akademia Maju, 2025)
This study explored the impact of the implementation of the National Competency Framework (KKNI), block learning system, and practicum reports on the learning stress of students at the Faculty of Mathematics and Natural Sciences (FMIPA) at Universitas Negeri Medan. A qualitative method was employed, utilizing in-depth interviews with five students, including two from the Mathematics Study Program, two from Chemistry, and one from Biology. The findings indicated that Biology students experienced lower stress levels compared to their peers in Chemistry and Mathematics. A better connection between theory and practice in biology education, along with stronger social support, contributed to the reduction of stress. In contrast, Mathematics and Chemistry students reported higher stress levels due to heavy academic demands and challenges in time management. Although the block learning system was designed to enhance focus, it increased pressure on students struggling to adapt. The study emphasized the importance of effective coping strategies and psychological support in managing stress. The findings aimed to assist the faculty in designing educational policies that address student needs, including improvements in facilities and psychological services. This research contributed to a better understanding of academic challenges in higher education and highlighted the significance of supporting students' mental well-being.